Lower Urinary Tract Symptoms and Sexual Dysfunction in Male: A Systematic Review and Meta-Analysis - Song, Guoda; Wang, Min; Chen, Bingliang; Long, Gongwei; Li, Hao; Li, Rui; Liu, Zhuo; Wei, Chao; Wang, Tao; Wang, Shaogang; Liu, Jihong; Zhang, Yucong; et al. (Frontiers in Medicine, 2021)
Background: An association between lower urinary tract symptoms (LUTS) and risk of sexual dysfunction in male remains controversial in recent decades. Materials and Methods: PubMed and Web of Science were searched up to October 28, 2020, for articles reporting the prevalence of sexual dysfunction in men with LUTS. The main outcomes were results from sexual dysfunction assessments. Pooled odds ratio (OR) and weighted mean difference (WMD) with 95% confidence interval (CI) were calculated. The quality assessment of the included studies was performed by using The Newcastle-Ottawa Scale (NOS) or JBI Meta-Analysis of Statistics Assessment and Review Instrument (JBI-MAStARI). Results: A total of 24 full-manuscript papers met the inclusion criteria. The pooled OR for 21 studies suggested that patients with severer LUTS had a higher risk of sexual dysfunction (OR = 3.31, 95% CI: 2.43 to 4.49, p < 0.001, I2 = 90%). A significant decrease in scores of assessment tools for sexual dysfunction was observed in the patients with higher severity of LUTS compared with those patients with lower severity (WMD = −5.49, 95%CI: −7.25 to −3.27, P < 0.001, I2 = 96%). Similar outcomes were also found in subgroup analyses. In a detailed analysis of specific sexual function domains, the severity of LUTS was associated with erectile dysfunction, intercourse satisfaction, and overall satisfaction, except for sexual desire. Conclusion: The study demonstrates an association between exposure of lower urinary tract symptoms and risk of sexual dysfunction in male. Assessment of sexual function is necessary for patients with lower urinary tract symptoms. Systematic Review Registration:http://www.crd.york.ac.uk/prospero, identifier: CRD42020208747.